Capacity and Readiness of Civil Society Organisations to Implement Community Case Management of Malaria in Kenya - Marita, Enock; Oule, Jared; Mungai, Margaret; Thiam, Sylla; Ilako, Festus (Pan African Medical Journal)
Introduction: Civil Society Organizations (CSOs) contribute to achieving development goals through advocacy, social mobilisation and provision of health services. CSO programming is a key component of Global Fund (GF) grants; however, CSOs face technical and governance capacity challenges in grant utilisation leading to missed opportunities for improving health at community level. Amref Health Africa was appointed Principal Recipient of a GF grant aimed at scaling up community case management of malaria through CSOs as sub-recipients in western Kenya. To identify potential risks and strengthen grant management, Amref Health Africa and the Ministry of Health conducted a capacity needs assessment to determine the capacity of CSOs to effectively utilise grants. Methods: 26 selected CSOs participated in this study. Document reviews and on-site assessments and observations were conducted using structured tool. The five main assessment areas were: governance and risk management; strategic and operational planning; monitoring and evaluation; programme management; and financial management. Overall performance was grouped into four categories: 3.0-2.5 (excellent), 2.0-2.4 (good), 1.5-1.9 (fair), and 1.0-1.4 (poor). Data were collected and analysed using Excel software. Results: twenty five out of 26 CSOs were legally compliant. 14(54%) CSOs were categorized as good; 7(27%) as excellent; 3(12%) as poor and 2(8%) as fair. Most CSOs had good programme management capacity but monitoring and evaluation presented the most capacity gaps. Conclusion: more than 75% of the CSOs were rated as excellent or good. A capacity building plan, programme risk management plan and oversight mechanisms were important for successful grant implementation.
© Enock Marita et al. The Pan African Medical Journal - ISSN 1937-8688. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Capacity assessment; Risk management; Malaria case management; Civil society organisations; Capacity building; Governance